Correlation between preoperative inflammatory markers, Ki-67 and the pathological grade of glioma. Issue 36 (10th September 2021) - Xu, Guangda; Li, Chengxue; Wang, Yanguo; Ma, Jinan; Zhang, Junchen
Abstract : Abstract: To investigate the correlation between preoperative inflammatory markers, Ki-67 expression and the pathological grade of glioma, and to provide a reference for clinical prediction of glioma prognosis. A total of 45 glioma patients who underwent surgery with complete clinical and pathological data were in our hospital from January 2012 to December 2018 were enrolled. Glioma was divided into WHO grade I to IV. Forty-five healthy health examiners with matched clinical characteristics were included to the control group. Blood routine tests were recorded at admission in both the glioma and control group. The ratio of neutrophil to lymphocyte cytometry (NLR), derived neutrophil to lymphocyte ratio (dNLR) (white blood cell count – neutrophil count to neutrophil count), platelet to lymphocyte ratio (PLR) and prognostic nutritional index (PNI, serum albumin content + 5 × lymphocyte count) were calculated. The expression of Ki-67 in glioma was detected by immunohistochemistry. The relationship between the above markers, Ki-67 expression and pathological grade of glioma was evaluated with receiver operating characteristics curve analysis and Spearman correlation test. The correlation between the markers and Ki-67 were also determined. NLR, dNLR, PLR were increased in the glioma group ( P < .001, <.001, .002), whereas red blood cell distribution width (RDW) was decreased ( P = .009). All the glioma samples expressed Ki-67 with varying degree. Receiver operating characteristics curve analysis reveals NLR, dNLR, PLR, and RDW have significant discriminating ability in differentiating the glioma and control sample. NLR, PLR, PNI, and Ki-67 were significantly correlated with glioma pathology grade ( P = .023, .006, .019, <.05), while dNLR and RDW were not associated with glioma grade. Finally, NLR and PLR were related to Ki-67 expression in glioma patients ( P = .002, .022), while dNLR and RDW were not related to Ki-67 expression. Preoperative inflammatory markers NLR, PLR, PNI, and postoperative Ki-67 expression are associated with pathological grade of glioma. Detection of these markers may aid in better prediction of glioma prognosis.